DETERMINASI KEBIJAKAN UTANG PERUSAHAAN - Arliansyah Arliansyah; Nur Afni Yunita; Miftahul Zannah Nasution (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study examines the impact of tangibility, free cash flow, growth, and profitability on debt policy. Samples are manufacturing firms listed on the Indonesian Stock Exchange during 2017-2019. Purposive sampling is employed to acquire 163 manufacturing firms for the 2017-2019 period. The classical assumption test consists of normality, autocorrelation, multicollinearity, and heteroscedasticity tests. And to test hypotheses consisting of the t (partial) test. The data were obtained from companies’ annual financial reports. The results showed that tangibility affects debt policy, but free cash flow, company growth, and profitability do not affect debt policy. The value of a coefficient determination in this research reflects 0.0265. It means that tangibility, free cash flow, growth, and profitability have the role of 2.65 % debt against its policies.